Evolving malice scoring models for ransomware detection: An automated approach by utilising genetic programming and cooperative coevolution. Issue 129 (June 2023) - John, Taran Cyriac; Abbasi, Muhammad Shabbir; Al-Sahaf, Harith; Welch, Ian; Jang-Jaccard, Julian
Abstract: Malice scoring is a technique that is present throughout the literature to quantify a software malignance through the assignment of a malice score. However, the majority of existing malice scoring models are synthesised using manually selected features and weights, where a domain specialist is needed. Hence, this paper aim at utilising Genetic Programming and cooperative coevolution to automatically evolve an ensemble of symbolic regression functions to assign a malice score to an instance of software data. Using a publicly available dataset, the effectiveness of the proposed method is assessed and compared to that of the state-of-the-art malice scoring method. The experimental results show that the proposed method has significantly outperformed the benchmark method and exhibits the best-performing model that produces an overall balanced accuracy of 95.80%, correctly classifying 94.21% and 97.39% of unseen malicious and benign instances, respectively. Furthermore, various aspects of the proposed method and experimental results have been analysed in-depth to provide insight into the evolutionary process and some of the automatically evolved models.